Agriculture sector reform and sectoral programs in Tajikistan - Goibov, Manuchehr; Khakimov, Parviz; Ashurov, Timur; Aliev, Jovidon (International Food Policy Research Institute, 2025)
Tajikistan’s agricultural sector, despite its challenging environment and limited natural resources, remains a vital component of the national economy, providing employment and income for a significant portion of the rural population. However, the sector faces critical challenges including inefficient land use, outdated farming practices, inadequate infrastructure, and the lingering influence of Soviet-era agricultural systems. Since the early 1990s, Tajikistan has embarked on a series of agricultural reforms aimed at improving productivity and sustainability. Key reforms include land redistribution, water sector restructuring, and the adoption of policies to modernize the agricultural sector. The “Agriculture Reform Program” (ARP) for 2012-2020 was a major initiative targeting structural changes in land and water management, as well as the reorientation of the Ministry of Agriculture from a central planning body to a facilitator and regulator.